PENGEMBANGAN E-BOOK BERMUATAN KEARIFAN LOKAL BALI NYEPI UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV SD - Evi Diona, Novanta; Yudiana, Kadek; Alit Wahyuni, Komang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low interest of students in learning the Social Science subject, especially the topics on the Benefits of Diversity and Preserving Cultural Diversity, is caused by the use of less innovative learning media and the lack of integration of local wisdom in teaching. This study aims to examine the design, test the validity, practicality, and effectiveness of an E-Book containing Balinese Nyepi local wisdom to increase the learning interest of 4th-grade elementary students. The uniqueness of this study lies in integrating the values of Balinese Nyepi local wisdom into digital learning media that are adapted to the characteristics of elementary school students. This study uses the ADDIE development model involving content experts, media experts, teachers, and students as trial subjects. The results show that the E-Book received a very good qualification with a validity score of 4.0 from content experts and 3.7 from media experts. The practicality level was 95.8% according to teachers, 91.6% in individual tests, and 89.87% in small group tests. Effectiveness analysis showed a significance value of 0.000 (p < 0.05). So, the Bali Nyepi local wisdom E-Book is feasible and effective to use to boost elementary students' interest in learning science.